Intermittent Oral Dosing of Roxadustat in Peritoneal Dialysis Chronic Kidney Disease Patients with Anemia: A Randomized, Phase 3, Multicenter, Open‐Label Study. Issue 2 (31st July 2019) - Akizawa, Tadao; Otsuka, Tetsuro; Reusch, Michael; Ueno, Mai
Abstract: Roxadustat is an oral hypoxia‐inducible factor prolyl hydroxylase inhibitor developed to treat anemia in chronic kidney disease (CKD) patients. This Phase 3, randomized, open‐label, 24‐week study investigated the efficacy and safety of roxadustat in Japanese CKD patients with anemia on peritoneal dialysis (PD) who were previously treated or not treated with erythropoiesis stimulating agents (ESAs). Patients not previously receiving ESA (ESA‐Naïve group) were randomized to roxadustat at a starting dose of 50 or 70 mg three times weekly; patients previously receiving ESA (ESA‐Converted group) switched from ESA to roxadustat 70 or 100 mg three times weekly depending on the prior ESA dose. Outcomes included maintenance rate of average hemoglobin (Hb) level within 10–12 g/dL at weeks 18–24, cumulative response rate at end of treatment (Hb thresholds, 10.0 g/dL or 10.5 g/dL; Hb increase, ≥1.0 g/dL), and average Hb levels at weeks 18–24. Safety was assessed by occurrence of treatment‐emergent adverse events (TEAEs). Fifty‐six patients were enrolled (ESA‐Naïve, n = 13; ESA‐Converted, n = 43). Maintenance rates (weeks 18–24) were 92.3% (95% CI: 64.0–99.8; ESA‐Naïve) and 74.4% (95% CI: 58.8–86.5; ESA‐Converted). Cumulative response rate was 100.0% in the ESA‐Naïve group. Average Hb levels (weeks 18–24) were 11.05 g/dL (95% CI: 10.67–11.42; ESA‐Naïve) and 10.93 g/dL (95% CI: 10.73–11.13; ESA‐Converted). Common TEAEs included nasopharyngitis and back pain. Roxadustat was well tolerated and effective in maintaining target Hb levels in CKD patients on PD who were previously treated or not treated with ESA.